Conserving the Tropical Rain Forest: A Critical Analysis of the Alternative Economic Policies - Torsten Amelung (ZBW - Leibniz Information Centre for Economics, 1990)
The tropical rainforests create positive external effects for the countries that go beyond the countries that host these rainforest. As a result, international trasfersshould be considered as adequate policy measures to compensate the tropical countries at least for the foregone benefits of the economic exploitation of the rainforests. Continuous periodical payments seem to be much more effective compared to once-for-all measures such as debt-for-nature swaps of or transitory development.
Keywords: 330; Deforestation; Climate Policies; International Co-operation